Plug-in electric vehicle diffusion in California: Role of exposure to new technology at home and work. (February 2022) - Chakraborty, Debapriya; Bunch, David S.; Brownstone, David; Xu, Bingzheng; Tal, Gil
Highlights: Neighborhood effect plays an important role in plug-in electric vehicle diffusion. Peer effect at the workplace has an important impact on the diffusion process. Positive effect of charging infrastructure on PEV sales. Targeted policies like Clean Car 4All can encourage PEV adoption. Abstract: The market for plug-in electric vehicles (PEVs) --including both battery electric vehicles (BEVs) and plug-in hybrid vehicles (PHEVs)--has been rapidly growing in California for the past few years. Given the targets for PEV penetration in the state, it is important to have a better understanding of the pattern of technology diffusion and the factors that are driving the process. Using spatial analysis and Poisson count models we identify the importance of a neighborhood effect (at home locations) and a workplace effect (at commute destinations) in supporting the diffusion of PEV technology in California between 2014 and 2016. In the case of new BEV sales, we find that exposure to one additional BEV or PHEV within a 1-mile radius of a census block group centroid is associated with a 0.2% increase in BEV sales in the block group. Interestingly, for new PHEV sales- the neighborhood effect of BEV sales is negative, suggesting that enhanced exposure to this type of technology (which is differentiated in distinctive ways from PHEVs) may impact new PHEV sales through a substitution effect. Specifically, higher BEV concentration in an area can have an overall negative effect on new PHEV sales. While the neighborhood effect at residential locations is important, a workplace effect also has a notably important influence on new PEV sales. Both effects work in combination with socioeconomic, demographic, policy, and built environment factors in encouraging PEV adoption. These results, insightful not just for California but other regions in early phases of the PEV market, suggest that policymakers should consider targeted programs and investments that can attract a wider group of early adopters (in terms of sociodemographic characteristics and spatial location) to boost the impact of neighborhood and workplace effects on PEV sales.